Types of Learning Media in Primary School during Covid-19 - Didik Efendi (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The Covid-19 pandemic required the learning process in primary schools in Jayapura to be conducted online. Each school has its policy for determining the learning media. This study aimed to describe how teachers specify the learning media and various types of media in primary schools during the Covid-19 pandemic. This study was descriptive qualitative research with data obtained through interviews, observations, documentation, and surveys through google forms. The research location consisted of MIN Kota Jayapura, MI Yaa Bunayya, and SDIT Qurrata A'yun in Jayapura. The results of the study show that in determining the learning media during the Covid-19 pandemic, teachers considered (1) learning objectives and teaching materials, (2) the learning style of students, (3) the ease of use of learning media for teachers, students and parents, (4) cost as a supporting factor in the process of determining the learning media since the economy level of the student's parents are different. The types of learning media in primary school during the Covid-19 pandemic consisted of visual-based learning media, audio-based learning media, and audio-visual-based learning media. In addition to these media, teachers collaborated with learning media such as WhatsApp, Google Classroom, Google Meet, Google Form, Zoom, Quizizz, and Wordwall. The obstacles faced by teachers when using these learning media were data packages, networks, the teacher's competence in using online learning media, and parents’ support at home in using online learning media.